Comparison of the gut microbiome and resistome in captive African and Asian elephants on the same diet - Feng, Xin; Hua, Rong; Zhang, Wanying; Liu, Yuhang; Luo, Caiyu; Li, Tonghao; Chen, Xiaolin; Zhu, Hui; Wang, Youcong; Lu, Yan (Frontiers in Veterinary Science, 2023)
Elephants are endangered species and threatened with extinction. They are monogastric herbivorous, hindgut fermenters and their digestive strategy requires them to consume large amounts of low quality forage. The gut microbiome is important to their metabolism, immune regulation, and ecological adaptation. Our study investigated the structure and function of the gut microbiota as well as the antibiotic resistant genes (ARGs) in captive Asian and African elephants on the same diet. Results showed that captive African and Asian elephants had distinct gut bacterial composition. MetaStats analysis showed that the relative abundance of Spirochaetes (FDR = 0.0) and Verrucomicrobia (FDR = 0.005) at the phylum level as well as Spirochaetaceae (FDR = 0.01) and Akkermansiaceae (FDR = 0.02) at the family level varied between captive African and Asian elephants. Among the top ten functional subcategories at level 2 (57 seed pathway) of Kyoto Encyclopedia of Genes and Genomes (KEGG) database, the relative gene abundance of cellular community-prokaryotes, membrane transport, and carbohydrate metabolism in African elephants were significantly lower than those in Asian elephants (0.98% vs 1.03%, FDR =0.04; 1.25% vs 1.43%, FDR = 0.03; 3.39% vs 3.63%; FDR =0.02). Among the top ten functional subcategories at level 2 (CAZy family) of CAZy database, MetaStats analysis showed that African elephants had higher relative gene abundance of Glycoside Hydrolases family 28 (GH 28) compared to Asian elephants (0.10% vs 0.08%, FDR = 0.03). Regarding the antibiotic resistance genes carried by gut microbes, MetaStats analysis showed that African elephants had significantly higher relative abundance of vanO (FDR = 0.0), tetQ (FDR = 0.04), and efrA (FDR = 0.04) than Asian elephants encoding resistance for glycopeptide, tetracycline, and macrolide/rifamycin/fluoroquinolone antibiotic, respectively. In conclusion, captive African and Asian elephants on the same diet have distinct gut microbial communities. Our findings established the ground work for future research on improving gut health of captive elephants.